Kompleksnaja ocenka sorevnovatel'noj dejatel'nosti i techniceskoj podgotovlennosti mnogoborcev v bar'ernom bege s ispol'zovaniem videoanaliza - Semaeva, G. N.; Kvashuk, P. V.; Kostyukov, P. P.; Rusakov, Yu. V.; Chernyshov, M. Yu.; Burlevich, V. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The paper presents the results of the development of criteria for assessing the special performance and functional status of elite BMX cyclists. Factor analysis in groups of men and women made it possible to identify 4 factors characterizing the structure of the functional state of BMX cyclists of high qualification in groups of men and women. The determining factors are: maximum anaerobic power; special (anaerobic) endurance; capacity of the lactate energy supply mechanism; functional state of the central nervous system and the rate of formation of sensorimotor reactions; fractional composition of labile components of body weight. Based on 5-point centile scales, criteria were developed for evaluating the special performance and functional status of elite BMX cyclists.